2018
DOI: 10.4049/jimmunol.1701695
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Validation of Rare Complement Variants Provides Insights into the Molecular Basis of Atypical Hemolytic Uremic Syndrome and C3 Glomerulopathy

Abstract: Atypical hemolytic uremic syndrome (aHUS) and C3 glomerulopathy (C3G) are associated with dysregulation and overactivation of the complement alternative pathway. Typically, gene analysis for aHUS and C3G is undertaken in small patient numbers, yet it is unclear which genes most frequently predispose to aHUS or C3G. Accordingly, we performed a six-center analysis of 610 rare genetic variants in 13 mostly complement genes (, ,, ,, ,, ,, ,, , and) from >3500 patients with aHUS and C3G. We report 371 novel rare va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
156
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 146 publications
(160 citation statements)
references
References 75 publications
3
156
0
1
Order By: Relevance
“…These results are consistent with the recently reported collaborative study looking at 3128 patients with aHUS from six centers. 18 In that study, CFB, THBD, CFHR5, and PLG showed insignificant burden for ultrarare variants compared with Exome Aggregation Consortium controls, suggesting that if these genes make any contribution to aHUS, it is small. In the absence of segregation and functional data, pathogenic mutations in CFB, THBD, CFHR5, and PLG should be reported with caution.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…These results are consistent with the recently reported collaborative study looking at 3128 patients with aHUS from six centers. 18 In that study, CFB, THBD, CFHR5, and PLG showed insignificant burden for ultrarare variants compared with Exome Aggregation Consortium controls, suggesting that if these genes make any contribution to aHUS, it is small. In the absence of segregation and functional data, pathogenic mutations in CFB, THBD, CFHR5, and PLG should be reported with caution.…”
Section: Discussionmentioning
confidence: 82%
“…In a study by Osborne et al, 39% of patients with aHUS harbored variants with an MAF,1.0%. 18 Applying this MAF to our cohort increases the rare variant carrier rate to 36% (144 patients), suggesting that lowering the MAF had a major impact. We recommend reviewing archived data and applying an MAF of 0.1% to refine the genetic diagnosis of aHUS.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Second, the actual pathogenetic and functional meaning of many mutations is still not defined. Finally, most genetic variants have a low penetrance, and combined variants may coexist, which also involves other genes, such as thrombomodulin (THBD) and diacylglycerol kinase-epsilon (DGKE) [55]. Thus, it is necessary to cautiously analyze the detected gene alterations to determine if they are specifically disease associated.…”
Section: Diagnosismentioning
confidence: 99%